OP0260 The pathophysiology of S100A8/A9 in familial mediterranean fever (FMF). (23rd January 2014) - Austermann, J.; Fassl, S.; Holzinger, D.; Chae, J.J.; Tilmann, K.; Keitzer, R.; Roth, J.; Foell, D.; Wittkowski, H.
Abstract : Background: Familial Mediterranean Fever (FMF) is an auto-inflammatory syndrome caused by mutations within the MEFV gene encoding pyrin protein. The FMF syndromeis associated with activation of phagocytic cells and secretion of IL-1β. The production and secretion of IL-1β is regulated by interactions of pyrin and the NALP3-inflammasome, but exact pathogenic mechanisms are still elusive. Like IL-1β, the pro-inflammatory Damage Associated Molecular Pattern (DAMP) molecules S100A8/A9 are released by a Golgi-independent but tubulin-dependent, so called alternative secretory pathway (1, 2). S100A8/A9 have been recently identified as endogenous activators of TLR4 and several studies on inflammatory disorders demonstrated their potential as biomarkers of inflammation (3). Objectives: Our goal was i) to correlate S100A8/A9 serum concentrations in FMF-patients to disease activity and to evaluate the potential of S100A8/A9 as biomarker, ii) to study S100A8/A9 -pyrin interaction, iii) to analyze S100A8/A9 serum-concentrations in FMF-mice. Methods: 52 genetically proven FMF-patients were studied longitudinally over 18 months. Serum-levels of S100A8/A9 (ELISA), ESR, CRP and SAA were analysed before and during colchicine treatment and compared to other autoinflammatory syndromes. S100A8/A9 serum-levels of homozygous Pyrin V726A knock-in mice ("FMF-mice") were determined for secretion analysis. Interaction and co-localization of S100A8/A9 and pyrin was analysed by immunofluorescence-, co-immunoprecipitation- and affinity-chromatography experiments. Results: The mean serum-levels of S100A8/A9 during inflammatory episodes of FMF (Mean ± SEM 343, 210±202, 210 ng/ml) were significantly higher compared to chronic infantile neurological, cutaneous and articular (CINCA) syndrome (2, 830±580 ng/ml; p<0.001) or Muckle-Wells syndrome (MWS) (3, 205±585 ng/ml; p<0.001), and correlated to disease activity. Similar, sera of homozygous FMF-mice showed increased S100A8/A9 -levels (1, 260±540 ng/ml) compared to WT- (150±40 ng/ml), or heterozygous FMF-mice (340±180 ng/ml). Immunofluorescence stainings of human monocytes showed a colocalisation of pyrin, S100A8/A9 and tubulin. Moreover a direct molecular interaction of pyrin with S100A8/A9 could be demonstrated in immunoprecipitation and affinity-chromatographyexperiments. Conclusions: S100A8/A9 are strongly secreted in FMF-patients compared to other IL-1 driven diseases. Measurement of S100A8/A9 -levels in FMF might be a valuable tool to reflect disease activity and response to anti-inflammatory therapy. Pyrin interacts directly with S100A8/A9 pointing towards an important role in the alternative secretion of those proteins in FMF. References: Vogl et al. (2007) Nat. Med. 13, 1042-1049. Rammes et al. (1997) J. Biol. Chem. 272, 9496-9502. Frosch et al. (2000) Arthritis Rheum. 43, 628-637. Disclosure of Interest: None Declared